Clinical and Genetic Predictors of Priapism in Sickle Cell Disease: Results from the Recipient Epidemiology and Donor Evaluation Study III Brazil Cohort Study. Issue 12 (24th October 2019) - Cintho Ozahata, Mina; Page, Grier P.; Guo, Yuelong; Ferreira, João Eduardo; Dinardo, Carla Luana; Carneiro-Proietti, Anna Bárbara F.; Loureiro, Paula; Mota, Rosimere Afonso; Rodrigues, Daniela O.W.; Belisario, André Rolim; Maximo, Claudia; Flor-Park, Miriam V.; et al.
Abstract: Introduction: Priapism is the persistent and painful erection of the penis and is a common sickle cell disease (SCD) complication. Aim: The goal of this study was to characterize clinical and genetic factors associated with priapism within a large multi-center SCD cohort in Brazil. Methods: Cases with priapism were compared to SCD type-matched controls within defined age strata to identify clinical outcomes associated with priapism. Whole blood single nucleotide polymorphism genotyping was performed using a customized array, and a genome-wide association study (GWAS) was conducted to identify single nucleotide polymorphisms associated with priapism. Main Outcome Measure: Of the 1, 314 male patients in the cohort, 188 experienced priapism (14.3%). Results: Priapism was more common among older patients ( P  = .006) and more severe SCD genotypes such as homozygous SS ( P < .0001). In the genotype- and age-matched analyses, associations with priapism were found for pulmonary hypertension ( P  = .05) and avascular necrosis ( P  = .01). The GWAS suggested replication of a previously reported candidate gene association of priapism for the gene transforming growth factor beta receptor 3 ( TGFBR3 ) ( P  = 2 × 10 −4 ). Clinical Implications: Older patients with more severe genotypes are at higher risk of priapism, and there is a lack of consensus on standard treatment strategies for priapism in SCD. Strengths & Limitations: This study characterizes SCD patients with any history of priapism from a large multi-center cohort. Replication of the GWAS in an independent cohort is required to validate the results. Conclusion: These findings extend the understanding of risk factors associated with priapism in SCD and identify genetic markers to be investigated in future studies to further elucidate priapism pathophysiology.